The Trini Sing-Song: Sociophonetic variation in Trinidadian English prosody and differences to other varieties1. (December 2022) - Meer, Philipp; Fuchs, Robert
The current study provides a phonetic perspective on the questions of whether a high degree of variability in pitch may be considered a characteristic, endonormative feature of Trinidadian English (TrinE) at the level of speech production and contribute to what is popularly described as 'sing-song' prosody. Based on read and spontaneous data from 111 speakers, we analyze pitch level, range, and dynamism in TrinE in comparison to Southern Standard British (BrE) and Educated Indian English (IndE) and investigate sociophonetic variation in TrinE prosody with a view to these global F0 parameters. Our findings suggest that a large pitch range could potentially be considered an endonormative feature of TrinE that distinguishes it from other varieties (BrE and IndE), at least in spontaneous speech. More importantly, however, it is shown that a high degree of pitch variation in terms of range and dynamism is not as much characteristic of TrinE as a whole as it is of female Trinidadian speakers. An important finding of this study is that pitch variation patterns are not homogenous in TrinE, but systematically sociolinguistically conditioned across gender, age, and ethnic groups, and rural and urban speakers. The findings thus reveal that there is a considerable degree of systematic local differentiation in TrinE prosody. On a more general level, the findings may be taken to indicate that endonormative tendencies and sociolinguistic differentiation in TrinE prosody are interlinked.